PRAGMATIK LINTAS BUDAYA: ANALISIS STRATEGI KESANTUNAN DALAM INTERAKSI ANTARBUDAYA - Umrah, Umrah; Saleh, Muhammad (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2025)
Cross-cultural pragmatics focuses on how differences in values, norms, and communication habits influence the use of politeness strategies in interactions between speakers from different cultures. These variations in language often lead to misunderstandings when the communication strategies used do not match the expectations of other cultures. This mismatch is evident in speech acts such as refusal, criticism, and responses to praise, which are interpreted differently by each culture. The success of cross-cultural communication greatly depends on the ability to understand the socio-cultural context, adjust speech style, and maintain harmony through appropriate politeness strategies. Cross-cultural pragmatic competence is key to creating effective, mutually respectful, and conflict-free interactions in intercultural encounters.